2016
DOI: 10.1007/s00520-016-3406-9
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care consultation team on acute wards—an intervention study with pre-post comparisons

Abstract: ᅟThere is little evidence regarding primary healthcare team members’ perceptions concerning palliative care consultation team (PCCT) and palliative care (PC) issues on their own wards.PurposeThis study aimed to study whether a PCCT can influence and change primary healthcare team members’ perceptions regarding the palliative care at the end of life they are providing to patients in their own acute wards.MethodsThe intervention was a PCCT visiting surgical and internal medicine wards in 1 year. We used a quasi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 33 publications
2
17
0
1
Order By: Relevance
“…Participants stressed that they had gained an increased awareness of their own professional role and the results reflected beliefs about both strengths and weaknesses in how to manage contacts with patients with palliative care needs, which can be assumed to be a start towards developing a common method of working [ 19 ]. This is also supported by Friedrichsen et al [ 31 ] who reported that professionals’ perceptions in regard to palliative measures could change following implementation of palliative care specialist consultations; to which our study contributes with a suggestion for how beliefs can change.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Participants stressed that they had gained an increased awareness of their own professional role and the results reflected beliefs about both strengths and weaknesses in how to manage contacts with patients with palliative care needs, which can be assumed to be a start towards developing a common method of working [ 19 ]. This is also supported by Friedrichsen et al [ 31 ] who reported that professionals’ perceptions in regard to palliative measures could change following implementation of palliative care specialist consultations; to which our study contributes with a suggestion for how beliefs can change.…”
Section: Discussionsupporting
confidence: 88%
“…Previous implementation of palliative care has shown positive results [ 31 , 35 37 ] as was also shown in this study since it was believed that participants felt more confident when their knowledge and their presence seemed to influence patients and their families. However, even after implementation, it was believed that structure and routine were still lacking in the day-to-day work with patients with palliative care needs.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Die Akzeptanz der PMD im eigenen Haus nimmtnach deren eigener Einschätzungweiter zu. Dies deckt sich mit früheren Berichten, die zeigen, dass sich im Krankenhaus tätige Palliativdienste durchgehend gut etablieren, nicht zuletzt aufgrund des Mehrwerts für die Patientenbetreuung, der von den einzelnen Fachabteilungen meist rasch erkannt wird [17][18][19][20]. Auch die tendenziell zunehmende Einbeziehung in Gespräche zu Therapiezieländerungen (▶ Abb.…”
Section: Akzeptanz Und Personelle Zusammensetzungunclassified
“…Therefore, National Health Insurance (NHI) developed the Hospice Shared-care Program to improve the rate of hospice care use in Taiwan since 2011, to enable patients who need hospice care to be cared for by hospice care teams in acute wards instead of limiting care to hospice wards. It was hoped that through discussions with hospice teams, the correct knowledge of hospice care could be obtained, and the utilization rate of hospice could be increased [18][19][20].…”
Section: Introductionmentioning
confidence: 99%